2019
DOI: 10.3390/w11071431
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Pollutant Residence Time and NO3 Concentrations in the Yucatan Karst Aquifer; Considerations for an Integrated Karst Aquifer Vulnerability Methodology

Abstract: Karst aquifers are a major source of drinking water with intrinsic features that increase the pollution risk from anthropogenic and natural impacts. In Yucatan, Mexico, groundwater is the sole source of drinking water, also acting as receptor of untreated wastewater due to the low regional coverage of sewer systems. To protect karst groundwater, vulnerability methodologies are widely used. Worldwide, multiple karst vulnerability schemes have been developed and tested; however, none of these consider pollutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…They also noticed that the shallow aquifer was more affected than the deeper aquifer. In the coastal aquifer of northern Yucatan, Martínez-Salvador et al (2019) reported that NO 3 concentration increases with recharge (July to November), providing evidence, that recharge plays an important role in dissolved substances' behaviour. Wet and cold season correspond to dates where rains were present in the zone; thus, it is possible that there was recharge.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They also noticed that the shallow aquifer was more affected than the deeper aquifer. In the coastal aquifer of northern Yucatan, Martínez-Salvador et al (2019) reported that NO 3 concentration increases with recharge (July to November), providing evidence, that recharge plays an important role in dissolved substances' behaviour. Wet and cold season correspond to dates where rains were present in the zone; thus, it is possible that there was recharge.…”
Section: Discussionmentioning
confidence: 95%
“…When hydrogeological parameters are well known, intrinsic vulnerability indexes such as DRASTIC can also be used for water management purposes (Jang et al, 2017;Hosseini and Saremi, 2018). We did not used a vulnerability index; however, the thin soil and porous epikarst features present in the study area, suggest that they are not acting as buffer zone (Martínez-Salvador et al, 2019); thus, they the movement of pollutants can occur fast. The shallow, unconfined aquifer ( 30 m deep) is embedded in a platform of carbonate sedimentary exposed rock (Andrade-G omez et al, 2019), and this dominance of bicarbonate, calcium, sulphate and sodium indicate rock dissolution, a dominant hydrochemical process.…”
Section: Discussionmentioning
confidence: 99%
“…It is also an important indicator of groundwater susceptibility to anthropogenic contamination [36]. Residence time is usually assessed in a distributed way [37,38], but it can also be estimated in a lumped way by applying simple index approximations, such as the turnover time index (T index), which expresses the ratio between storage (S), and recharge (R) [20,39]. It is related to the resilience of groundwater bodies to temporal pumping increases.…”
Section: Introductionmentioning
confidence: 99%
“…Distributed approximations of residence time have been employed to assess and validate intrinsic groundwater vulnerability in several studies [22,23,37]. These distributed approaches, more precise and detailed than lumped approaches, demand higher computational efforts and need data that are not always available, which makes it impossible to use a single method to validate the vulnerability maps from different case studies [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In Kenya, these types of data are not available or partially available from project output (difficult to find and obtain) or from a global dataset (based on estimations and not fully reliable). Alternative methods [36,37] require the characteristics of the hazard, i.e., nitrate source yields which are also unknown. In general, therefore, in North Horr Sub-County high spatial and high temporal resolution data, as well as point data, are scarce.…”
Section: Introductionmentioning
confidence: 99%